Екологічне миробудівництво як механізм сталого розвитку в умовах особливого періоду - Жарова, Л.В. (Економіка природокористування і охорони довкілля, 2016)
Розкрито значення термінів миробудівництва і трансформації конфлікту та їх використання в українській практиці. Досліджено історію виникнення і досвід поширення цих понять. Визначено різницю між розв’язанням і трансформацією конфлікту та ефективність імплементації цих різних підходів. Обґрунтовано ймовірність трактування особливого періоду, що є законодавчо закріпленим терміном, як періоду трансформації конфлікту в частині соціально-економічних та інституційно-політичних дій. Розглянуто можливість і доцільність застосування екологічного миробудівництва на тлі соціально-економічного відродження непідконтрольних і тимчасово окупованих територій. Досліджено міжнародний досвід трансформації конфлікту на основі розглянутих методик. In the article the meaning of the terms peacebuilding and conflict transformation are highlighted and their applicability for Ukrainian situation is examined. Results of research about appearance and implementation of mention terms in historical framework is represented. Represented research pays attention to practical aspects and experience of cooperation and collaboration of international institutions and cooperatives of various organizations, companies, and foundations in terms of environmental peacebuilding and conflict transformation. Also, the possibilities for Ukrainian inclusion into these processes are examined. The difference between conflict management and conflict transformation is defined and effectiveness of the implementation of these approaches is illustrated. The possibility of interpretation the special period as legislated term as conflict transformation period in social, economic, institutional and political framework is grounded. The possibility and feasibility of environmental peacebuilding as the backdrop of socio-economic recovery of beyond of the control and temporarily occupied territories is researched. The international experience of conflict transformation based techniques is examined.